Investigation of new inflammatory biomarkers in patients with brucella - Canpolat Erkan, Revşa Evin; Tekin, Recep (PloS one, 2024)
Delayed diagnosis and inadequate treatment of infectious and inflammatory diseases, such as Brucella, lead to high rates of mortality and morbidity. The aim of our study was to investigate the association between serum levels of apelin, presepsin, and irisin with inflammation, laboratory parameters, and blood culture in patients with brucella. This prospective case-control study involves 30 patients with brucellosis and 30 healthy, matched control subjects. Thirty patients who were diagnosed with brucellosis were aged ≥ 18 years. Blood samples were taken from the patients on the first day they were diagnosed with brucellosis. The values of irisin, presepsin, and apelin were studied. In addition, blood samples were also taken from 30 healthy individuals for the control group. Irisin, presepsin, and apelin values that were measured in the patients on the first day were compared with those values measured in the control group. The sex and age statuses of the subjects are matched among the groups. The levels of irisin were significantly higher in patients with brucellosis compared to the control group (p<0.045). There was no significant difference between the two groups in terms of apelin and presepsin levels (p values 0.087 and 0.162, respectively). There was a positive correlation between irisin levels and elevated ALT levels, as well as positive blood cultures. It appears that the measurement of irisin levels may be beneficial in patients with brucellosis. Irisin can be used as a diagnostic marker for brucella infection and may greatly clinicians to predict the severity disease and treatment response.